Comprehensive Study on Impact of Inserted Nanoparticles with Base Fluid on Heat Transfer Enhancement in Various Configurations - Ahmed Ali, Sarmad (Journal of Advanced Mechanical Engineering Applications, 2025)
Many industrial and engineering applications have low thermal conductivity that affects heating or cooling processes, so the heat transfer process for these applications will be optimized by using small nanometer-sized particles such as metal, oxide, carbide, etc. dispersed in the basic fluid of the application, these particles are called nanofluids. This paper reviews the varying factors affecting the thermal conductivity of various nanomaterials under different conditions. All the authors focused on the thermal conductivity of nanoparticles to increase the heat transfer process, whereby increasing the percentage of nanoparticles, the thermal conductivity increases, and therefore the performance and efficiency of thermal systems increases. The size, shape, collision, aggregation, porous layer, melting point of nanoparticles, etc. are all parameters that affect the thermal conductivity of the nanomaterial, and their control determines the behavior of its increase or decrease. The use of nanofluid is a new and influential technology to improve heat transfer for the next generation. The results of the study indicated that the nanomaterial has an effect on increasing thermal conductivity by significantly raising the efficiency of thermal conductivity of the liquid and improving thermal convection, where the Brownian motion of nanoparticles contributes to improving thermal convection inside the liquid as well as reducing thermal resistance.